2006
DOI: 10.1093/toxsci/kfl036
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Prepubertal Female Rats to Inhaled Di(2-ethylhexyl)phthalate Affects the Onset of Puberty and Postpubertal Reproductive Functions

Abstract: We evaluated the effects of inhaled di(2-ethylhexyl)phthalate (DEHP) on the onset of puberty and on postpubertal reproductive functions in prepubertal female rats. DEHP was administered by inhalation at doses of 0, 5, and 25 mg/m3 to groups of female rats for 6 h/day, 5 contiguous days/week from postnatal days (PNDs) 22 to 41 and to PND 84. The onset of puberty was determined by daily examination for vaginal opening (VO) and first estrous cycle. Reproductive function was evaluated by observing estrous cyclicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 33 publications
0
65
0
Order By: Relevance
“…Specifically, ex vivo production of LH was increased in gonadotropes obtained from DEHP-treated immature rats while serum progesterone levels were decreased (Svechnikova et al 2007). However, a different study showed that inhaled DEHP (5 and 25 mg/m 3 ) increased levels of LH and E 2 in serum of prepubertal rats, and it increased ovarian Cyp19a1 expression (Ma et al 2006), the latter two in disagreement with more recent findings. Perhaps this difference is due to differences in the experimental approaches used (in vivo versus in vitro) as well as exposure routes and doses given.…”
Section: Plasticizers: Bisphenol a And Phthalatesmentioning
confidence: 57%
“…Specifically, ex vivo production of LH was increased in gonadotropes obtained from DEHP-treated immature rats while serum progesterone levels were decreased (Svechnikova et al 2007). However, a different study showed that inhaled DEHP (5 and 25 mg/m 3 ) increased levels of LH and E 2 in serum of prepubertal rats, and it increased ovarian Cyp19a1 expression (Ma et al 2006), the latter two in disagreement with more recent findings. Perhaps this difference is due to differences in the experimental approaches used (in vivo versus in vitro) as well as exposure routes and doses given.…”
Section: Plasticizers: Bisphenol a And Phthalatesmentioning
confidence: 57%
“…In a study of prepubertal rats, researchers observed accelerated puberty, as determined by early vaginal opening and first estrous cycle, and significantly increased cholesterol, luteinizing hormone (LH) and estradiol after exposure to DEHP via inhalation (Ma, et al 2006). The authors suggested that DEHP may induce LH secretion by the pituitary, altering pubertal development.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the evidence of neuroendocrine effects is lying on reduced fibers immunopositive for Kiss-1 (Losa et al, 2011 ;Bateman and Patisaul, 2008) which is inconsistent with early sexual maturation as opposed to increased FOS expression in GnRH neurons (Losa et al, 2011;Bateman and Patisaul, 2008). Using phthalates, the period of exposure appears crucial since prenatal exposure accounts for late VO (Salazar et al, 2004) whereas postnatal exposure is associated with normal timing (Gray et al, 2006;Moral et al, 2007) or early VO irrespective of the dose (Hu et al, 2013;Ma et al, 2006). Here, the complexity of neuroendocrine mechanisms appears since, in conditions causing early puberty, the arcuate nucleus expression of Kiss1 mRNA and kisspeptin protein is increased but the receptor GPR54 mRNA expression is reduced (Hu et al, 2013;Ma et al, 2006).…”
Section: Female Rodentmentioning
confidence: 99%
“…Using phthalates, the period of exposure appears crucial since prenatal exposure accounts for late VO (Salazar et al, 2004) whereas postnatal exposure is associated with normal timing (Gray et al, 2006;Moral et al, 2007) or early VO irrespective of the dose (Hu et al, 2013;Ma et al, 2006). Here, the complexity of neuroendocrine mechanisms appears since, in conditions causing early puberty, the arcuate nucleus expression of Kiss1 mRNA and kisspeptin protein is increased but the receptor GPR54 mRNA expression is reduced (Hu et al, 2013;Ma et al, 2006). Polybromi-nated EDCs appear to cause either no change or delay in VO depending on the dose and irrespective of the period of exposure (Stoker et al, 2004;Lilienthal et al, 2006;Ceccatelli et al, 2006).…”
Section: Female Rodentmentioning
confidence: 99%